2015
DOI: 10.1111/pce.12594
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced leaf photosynthesis as a target to increase grain yield: insights from transgenic rice lines with variable Rieske FeS protein content in the cytochrome b6/f complex

Abstract: Although photosynthesis is the most important source for biomass and grain yield, a lack of correlation between photosynthesis and plant yield among different genotypes of various crop species has been frequently observed. Such observations contribute to the ongoing debate whether enhancing leaf photosynthesis can improve yield potential. Here, transgenic rice plants that contain variable amounts of the Rieske FeS protein in the cytochrome (cyt) b6 /f complex between 10 and 100% of wild-type levels have been u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
66
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(72 citation statements)
references
References 67 publications
(68 reference statements)
5
66
0
1
Order By: Relevance
“…Accordingly, for the three Sedum species, the comparisons of the photosynthetic and transpiration rates between C3 and CAM plants require further investigation. The photosynthetic rates of vegetation plants have a close relationship with carbon sequestration (Yamori et al, 2016). In addition, previous studies have demonstrated that evapotranspiration is the most important contributing factor toward the cooling effect in green roofs (Takakura et al, 2000;Oberndorfer et al, 2007;Feng et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, for the three Sedum species, the comparisons of the photosynthetic and transpiration rates between C3 and CAM plants require further investigation. The photosynthetic rates of vegetation plants have a close relationship with carbon sequestration (Yamori et al, 2016). In addition, previous studies have demonstrated that evapotranspiration is the most important contributing factor toward the cooling effect in green roofs (Takakura et al, 2000;Oberndorfer et al, 2007;Feng et al, 2010).…”
Section: Discussionmentioning
confidence: 98%
“…Evidence to support this has come from the theory and modeling of the photosynthetic process, growth of plants in elevated CO 2 , and transgenic manipulation (Zhu et al, 2010). It was shown previously in antisense studies that reducing the levels of the Rieske FeS protein resulted in a reduction in levels of the cyt b 6 f complex, a decrease in photosynthetic electron transport, and, in rice (Oryza sativa), a decrease in both biomass and seed yield (Price et al, 1998;Yamori et al, 2016). These findings identified the cyt b 6 f complex as a limiting step in electron transport and would suggest that overexpression of the Rieske FeS protein may be a feasible route to increase photosynthesis and yield.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous research which showed that green perilla cultivars generally grow faster than red ones in open fields (Martinetti et al, 2012). The difference in productivity may be due to the difference in photosynthetic capacity between green perilla and red perilla ( Figure 3 ), since plant growth largely depends on photosynthesis (Yamori, 2016; Yamori and Shikanai, 2016; Yamori et al, 2016). The higher photosynthetic capacity of green perilla reflected in higher net photosynthetic rate, stomatal conductance, and ETR per unit leaf area, compared to those in red perilla ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%